Pengaruh Perubahan Pendapatan Bunga Bersih dan Size terhadap Expected Return Saham pada Perusahan Perbankan di BEI Tahun 2006 – 2010 - Harry Budiantoro (Majalah Sainstekes, 2017)
Information content from net interest income and size of entity have very important role to provide information for users to make decision in accordingly. For investor, information in financial statement moght be used to determine the risk rate in expected return. This research aims to testthe influence iterations of net interest income, and size toward share expected return in the banking company at BEI. In this study 14 samples of company available from industrial banking based ICMD 2010 during the period of 2006-2010 were analysed. Multiple linear regresion models was employed to test influence of net interest income and size toward share expected return. Result of classic assumption test abnormal distribution data showed no finding of any multi-collinear, heteroscedasticity, and autocorrelation. However the result showed share expected return was influenced simultaneuosly by PBB iteration, and size and partially no variable significantly influence expected return.